TiO2 Synthesis by Pechini Method and Application in Dye-Sensitized Solar Cells - Gideã Taques Tractz; Bianca Vanjura Dias; Guilherme Arielo Rodrigues Maia; Paulo Rogério Pinto Rodrigues (Orbital: The Electronic Journal of Chemistry, 2021)
Dye-sensitized solar cells (DSSC) are devices to solar energy conversion, which present low production costs and high photoelectrochemical stability. The aim of this study was to investigate the synthesis of TiO2 by Pechini methodology, using C12H28O4Ti and TiCl3 as precursors, and their application in solar cell sensitized by N719 dye. The characterization techniques employed were Scanning Electron Microscopy (SEM), UV-VIS Spectroscopy, X-ray diffraction (XRD), photochronoamperometry, j-V Curves and EIS plots. The results demonstrated a high crystallinity and surface area to particles obtained with C12H28O4Ti as precursor. The highest photoconversion energy efficiency reached was to TiO2 using C12H28O4Ti with PCE= 4.17±0.13% with photoelectrochemical parameters of jsc= 5.53 ±0.08, Voc= 0.78±0.07 FF=0.58±0.05 and less resistive to charge transport with τe= 53 ms.DOI: http://dx.doi.org/10.17807/orbital.v13i2.1446